Solution of heat equation by a novel implicit scheme using block hybrid preconditioning of the conjugate gradient method - Buranay, S. C.; Arshad, N. (Karaganda State Univ, 2023)
The main goal of the study is the approximation of the solution to the Dirichlet boundary value problem (DBVP) of the heat equation on a rectangle by developing a new difference method on a grid system of hexagons. It is proved that the given special scheme is unconditionally stable and converges to the exact solution on the grids with fourth order accuracy in space variables and second order accuracy in time variable. Secondly, an incomplete block factorization is given for symmetric positive definite block tridiagonal (SPD-BT) matrices utilizing a conservative iterative method that approximates the inverse of the pivoting diagonal blocks by preserving the symmetric positive definite property. Subsequently, by using this factorization block hybrid preconditioning of the conjugate gradient (BHP-CG) method is applied to solve the obtained algebraic system of equations at each time level.
6th International Conference on Analysis and Applied Mathematics (ICAAM) -- OCT 31-NOV 06, 2022 -- Antalya, TURKEY
Keywords: Heat equation; implicit scheme; hexagonal grid; stability analysis; symmetric positive definite matrix; approximate inverse; incomplete block factorization; block hybrid preconditioning; conjugate gradient method